Nutritional parenting patterns and their determinants among PKH beneficiaries in Ruteng Sub-District - Jehuman, Engelina Suryawaty; Padmawati, Retna Siwi; Daniel (Universitas Gadjah Mada, 2024)
Purpose: To explore the nutritional parenting practices and their determinant factors among beneficiaries of the Family Hope Program (PKH) in Ruteng Sub-District. Methods: This study is qualitative research with a case study design using a snowball sampling technique. The primary informants of the study are parents of toddlers who are beneficiaries of the Family Hope Program. Data is collected through focus group discussions, in-depth interviews, observations, and document studies. Results: Incorrect timing of complementary feeding is still common, and lack of dietary variety and insufficient protein consumption are prevalent issues in the community. The behaviour of proper waste disposal remains very low; the attendance rate of parents at posyandu and receiving immunizations still needs to improve, at 71% or below the standard. Regarding the determinant factors of parenting practices, it is known that most mothers are over 35 years old, parents have a low educational level, and parents' occupations consume their time, large families, and husbands' limited involvement in child care, cultural and habitual factors are also known to influence the parenting practices. Conclusion: The nutritional parenting practices for toddlers among PKH beneficiaries in the Ruteng Sub-District still need to be improved, particularly in providing complementary feeding, feeding practices, hygiene and sanitation, and child healthcare maintenance. Several determinants influence these nutritional parenting practices, such as the mother's age, low educational level, parents' occupations, large family size, cultural factors, and low support from husbands in the child-rearing process.